COVID-19 et manifestations au balcon - Jeanne Ferrari-Giovanangeli (Communication)
This first-person account puts readers in the mind of someone who, though confined, is able to peer through the windows to see—and willfully enter into—the full depth and breadth of an ethnographic field. This narrative revisits an ethnographic field experience and combines the theory and empirical approach of communication anthropology. The goal is to go beyond thinking about why a culture engages in certain rituals to question the intricacies of culture as a whole